Some Fixed Point Theorems for \((α,β,z)\)-Contraction Mapping under Simulation Functions in Banach Space - Dwivedi, Snehlata; Mishra, Urmila; Dubey, A.K.; Pandey, M.D. (Communications in Mathematics and Applications, 2023)
In this paper, we prove some fixed point results in the setting of a Banach space via a cyclic \((α ,β ,z)\)-admissible mapping imbedded in simulation function. Our results extend and generalize some well known results in the existing literature.
Keywords: Banach space; Fixed point; \((α ,β ,z)\)-admissible mapping; Simulation functions